Telemedicine in geriatric oncology is here to stay - Alexander, Koshy; Tin, Amy L.; McMillan, Sincere; Amirnia, Farnia; Yulico, Heidi; Sun, SungWu; Korc Grodzicki, Beatriz (Frontiers in Medicine, 2024)
Introduction: Advancing age is the most important risk factor for cancer. Collaborations with medical and surgical-oncology divisions, and supportive services are required to assist older adults with cancer through their assessment and treatment trajectories. This often requires numerous clinical encounters which can increase treatment burden on the patient and caregivers. One solution that may lighten this load is the use of telemedicine.Methods: At Memorial Sloan Kettering, the Cancer and Aging Interdisciplinary Team (CAIT) clinic risk stratifies and optimizes older adults planned for medical cancer treatment. We analyzed patients seen in the CAIT clinic between May 2021 and December 2023, focusing on their utilization of telemedicine, and on the differences in characteristics of the visits and the results of the Geriatric Assessment based on visit type.Of the 288 patients (age range 67-100) evaluated, the majority (77%) chose telemedicine visits. Older age, lower educational status, living in New York City, abnormal cognitive screen, impaired performance measures, IADL dependency and having poor social support were all associated with choosing an in-person visit as opposed to telemedicine.Older patients with cancer frequently choose and can complete telemedicine visits. Efforts should be directed to develop an infrastructure for remote engagement, improving reach into rural and underserved areas, decreasing the burden generated by multiple appointments.